2011
DOI: 10.1103/physrevb.83.064116
|View full text |Cite
|
Sign up to set email alerts
|

Annealing kinetics of latent particle tracks in Durango apatite

Abstract: Using synchrotron small angle X-ray scattering we determine the 'latent' track morphology and their annealing kinetics in the Durango apatite. The latter, measured during ex situ and in situ annealing experiments, suggests structural relaxation followed by recrystallisation of the damaged material. The resolution of fractions of a nanometer with which the track radii are determined, as well as the non-destructive, artefact-free measurement methodology shown here, provides a new means for in-depth studies of io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
56
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 24 publications
11
56
0
Order By: Relevance
“…An additional term was added when calculating the scattering intensity taking into account a roughening of the track boundaries during the annealing process [17],…”
Section: Annealing Kineticsmentioning
confidence: 99%
See 3 more Smart Citations
“…An additional term was added when calculating the scattering intensity taking into account a roughening of the track boundaries during the annealing process [17],…”
Section: Annealing Kineticsmentioning
confidence: 99%
“…Small angle X-ray scattering (SAXS) provides an alternative technique to study ion track damage as it measures density changes at the nanometre scale. We have recently demonstrated, that SAXS can provide previously unresolved details of the track structure in amorphous SiO 2 [14][15][16], metallic glasses, and natural apatite [17][18][19]. Using in situ and ex situ annealing experiments, we have demonstrated that SAXS is well suited for determining the annealing kinetics of ion tracks [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this facility it is also possible to generate ion tracks under high pressure and high temperature conditions. Previous studies in our group focussed on the variations in un-etched track morphology characterised by synchrotron based small angle x-ray scattering (SAXS) [3,4]. SAXS is a non-destructive technique used to study the size, orientation and spatial arrangement of nano-to micro-sized objects.…”
Section: Introductionmentioning
confidence: 99%